Uso del celular y calidad del sueño en adolescentes de bachillerato. Chambo, 2022 - Echeverria Salas, Karol Nicole (2022)
ABSTRACT: This research aimed to analyze the use of cell phones and the quality of sleep in adolescent students of the "Colegio de Bachillerato Chambo" of the Chambo canton. The methodology was carried out with a quantitative, documentary, and bibliographic approach, with a transversal and non-experimental design, with a descriptive and correlational level. The population consisted of 400 educational data of high school students provided by an anonymous database of the institution, of which 120 data were considered for the establishment of the sample, which was non-probabilistic by convenience. For the investigation of the variables of the study, documentary analysis was used as a technique. As an instrument, the data registration form was used to collect data on mobile device dependence (TDM) and sleep quality (PSQI) in adolescents to establish the relationship between the variables. Among the most relevant results, it was found that 48.3% had a moderate dependence on the mobile device, and 51.7% had a moderate level of severity concerning sleep quality. The Pearson correlation showed a statistically positive correlation between the variables with an Rho=.19 and a significance level of p<0.030, indicating that the greater the use of the cell phone, the greater the problems in sleep quality. Therefore, it can conclude that if adolescents continue to use smartphones uncontrolled, they have a high probability of triggering sleep disorders.